Dye-containing wastewater treatment by photo-assisted wet peroxidation using Au nanosized catalysts - Carmen Rodrigues (2018)
BACKGROUND:The aim of this study is to test different supports on which to deposit Au nanoparticles and to determine the most suitable for Orange II (OII) dye degradation by a photo-assisted wet peroxidation (PWPO) process. The catalysts used (Au-Fe2O3, Au-TiO2,Au-ZnO and Au-Al2O3) were prepared by the depositionprecipitation method; a reference catalyst from the World Gold Council, hereafter denoted as Au-Fe2O3*, was also used for comparison. The catalysts were characterized in terms of surface area (SBET), gold nanoparticles size, Au loading and Au oxidation state using several techniques (namely, nitrogen adsorption at 196C, X-ray photoelectron spectroscopy XPS, and high resolution transmission electron microscopy HR-TEM). Several runs were carried out for each material, to evaluate its efficiency in OII dye degradation by the PWPO process. RESULTS: All catalysts reached OII dye removals of >96% and considerable total organic carbon (TOC) degradation between 58.4% and 80.5%. The materials had negligible Au leaching, showing very good stability. For the catalyst with best performance (Au/Al2O3), a parametric study was carried out to assess the effect of different variables on dye and TOC removals.Under the best conditions, excellent efficiency of the advanced oxidation process was obtained. A simulated industrial acrylic dyeing effluent was also treated by PWPO and very good performance was reached, with removals up to 100%, 72.4% and 70.0% for color, TOC and COD, respectively, with only 2 h of reaction. Moreover, there was an improvement in biodegradability and a non-toxic effluent was generated. CONCLUSIONS: PWPO using nano-sized gold-based catalysts proved to be a promising technique for the degradation of pollutants in water. The used gold supports have an important role in the efficiency of the process. The best catalyst was obtained using large surface area Al2O3 as support, although no leaching of gold was found for any of the catalysts. The mineralization degree improved under radiation due the formation of hydroxyl radicals, being reached total dye removal and a decrease of the TOC values greater than 90%.